ANALISIS PENERIMAAN DAERAH DARI SEKTOR PARIWISATA DI KOTA KENDARI - Murriyanti, Witri Prastika; Muthalib, Abdul Azis; Ernawati, Ernawati (Pascasarjana Universitas Halu Oleo, 2017)
Analysis of regional revenue from tourism sector in Kendari City. This research aims of analize the influence of the number of tourism and the occupancy rate of the hotel to the tourism sector revenue in Kendari City.In this research use secondary data type with data on the number of tourists and the hotel occupancy rate of the year 2002-2016 Analyzer used in this research is doubled linear regression with reception area in the tourism sector as dependet variable and two independent variable is hotel accupancy rate number of tourism.After the test deviation of classical assumption, the result show data is normally distributed and no deviation is obtained. So it can be concluded that the independent variable that is the number of tourism and the occupancy rate of hotels together effect the revenue of the tourism sector in Kendari. Partially variable of number tourists and hotel accupancy rate have a significant effect.Based on the result of the analysis of the research then submitted suggestion to the local government of kendari city to further improve the facilities and treathment of tourism objectÂ better so it has the attraction to be visited by tourists both archipelago and abroad so as to increase the original revenue area kendari.Keywords : LocallyÂ generated revenue, Number of tourists , The occupancy rate of the hotel